Optical coherence elastography for strain dynamics measurements in laser correction of cornea shape. Issue 11 (11th May 2017) - Zaitsev, Vladimir Y.; Matveyev, Alexander L.; Matveev, Lev A.; Gelikonov, Grigory V.; Omelchenko, Alexander I.; Baum, Olga I.; Avetisov, Sergey E.; Bolshunov, Andrey V.; Siplivy, Vladimir I.; Shabanov, Dmitry V.; Vitkin, Alex; Sobol, Emil N.
Abstract: We describe the use of elastographic processing in phase‐sensitive optical coherence tomography (OCT) for visualizing dynamics of strain and tissue‐shape changes during laser‐induced photothermal corneal reshaping, for applications in the emerging field of non‐destructive and non‐ablative (non‐LASIK) laser vision correction. The proposed phase‐processing approach based on fairly sparse data acquisition enabled rapid data processing and near‐real‐time visualization of dynamic strains. The approach avoids conventional phase unwrapping, yet allows for mapping strains even for significantly supra‐wavelength inter‐frame displacements of scatterers accompanied by multiple phase‐wrapping. These developments bode well for real‐time feedback systems for controlling the dynamics of corneal deformation with 10–100 ms temporal resolution, and for suitably long‐term monitoring of resultant reshaping of the cornea. In ex‐vivo experiments with excised rabbit eyes, we demonstrate temporal plastification of cornea that allows shape changes relevant for vision‐correction applications without affecting its transparency. We demonstrate OCT's ability to detect achieving of threshold temperatures required for tissue plastification and simultaneously characterize transient and cumulative strain distributions, surface displacements, and scattering tissue properties. Comparison with previously used methods for studying laser‐induced reshaping of cartilaginous tissues and numerical simulations is performed. Abstract : OCT images of an excised rabbit eye cornea before and after application of a non‐destructive laser‐reshaping procedure using an IR laser. The applied 50‐second pulse‐periodic laser‐induced moderate heating (∼45–55  ° C) made it possible to noticeably reshape cornea (e. g., produce/smoothen indentations) without causing tissue coagulation and worsening its optical properties. The inset shows examples of reconstructed dynamic (inter‐frame) and cumulative strains obtained during thermo‐mechanical smoothing of the indentation shown in the upper panels.